Exploration and Scarcity - Devarajan, Shantayanan; Fisher, Anthony C. (Journal of Political Economy, 1982)
[Noting that a suggested measure of natural resource scarcity, resource rent, is unobservable, we show that rent is linked to (observable) marginal exploration cost. A two-period model of extraction and exploration reveals that rent is equal to this cost when discovery is certain. Under risky exploration, cost data can be used to bound rent. The model also indicates how exploration uncertainty affects the competitive firm's extraction and exploration decisions. Finally, the behavior of U.S. oil and gas exploration costs suggests that these costs were rising in the postwar era, which has different implications for scarcity than indicated by other measures of scarcity.]